Outcome in Triple Valve Surgery: Our Experience - Gautam, N; Rajbanshi, B; Pradhan, S; Sharma, J; Koirala, R; Koirala, b (Nepalese Heart Journal, 2008)
Shahid Gangalal National Heart Centre does about 1200 cardiac operations per year. Valve Surgery especially for rheumatic valves comprises about half of the operations performed every year. Over 1500 valve surgeries have already been performed in the centre since 2002 till date. We present our experience on triple valve surgery.